2011
DOI: 10.7589/0090-3558-47.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Profiling of Yersinia Pestis Infection in the Wyoming Coyote (Canis Latrans)

Abstract: ABSTRACT:Although Yersinia pestis is classified as a ''high-virulence'' pathogen, some host species are variably susceptible to disease. Coyotes (Canis latrans) exhibit mild, if any, symptoms during infection, but antibody production occurs postinfection. This immune response has been reported to be against the F1 capsule, although little subsequent characterization has been conducted. To further define the nature of coyote humoral immunity to plague, qualitative serology was conducted to assess the antiplague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Coyotes infected with Y. pestis show few, if any, clinical signs (Vernati et al 2011; Baeten et al 2013). They become infected by consuming infected rodents or lagomorphs, or by being bitten by infected fleas (CDC, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Coyotes infected with Y. pestis show few, if any, clinical signs (Vernati et al 2011; Baeten et al 2013). They become infected by consuming infected rodents or lagomorphs, or by being bitten by infected fleas (CDC, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Rodents are natural hosts and suffer severe disease with high mortality, but some rodent predators such as dogs and coyotes experience only mild or in apparent disease [1][4], [33], [42], [43]. This variation in disease severity among susceptible hosts may be related to the extent to which Y. pestis overcomes the initial host macrophage mediated stress.…”
Section: Discussionmentioning
confidence: 99%
“…These coccobacilli eventually died within YCVs due to macrophage killing. This failure of Y. pestis to overcome macrophage imposed stress during the initial intracellular parasitism phase of plague may result in less severe disease in dogs and coyotes [1], [33], [42], [43].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of antibodies to Y. pestis proteins other than F1 may be useful in determining antibody prevalence in wild animals and avoiding false negative results. Vernati et al (2011) showed that 65% of coyote serum samples from Wyoming that were antibody-positive by ELISA using whole-cell extracts were negative for anti-F1 antibodies by Western blot. However, 90% of these samples were reactive with at least one other Y. pestis antigen, LcrV, YpkA, YopD, and Pla.…”
mentioning
confidence: 99%